2D/2D Hybrids: Re-visiting interfacial synthesis and charge-carrier dynamics for photocatalysis - Nurul Afiqah Mokri; Pei Ching Oh; Mohammad Khalid (Results in Engineering)
Early discovery on 2D materials such as graphene, graphitic carbon nitrides and titanium carbide-MXenes have inspired material scientist to develop newly 2D/2D hybrids. These classes of 2D material own a unique colloids-particle and molecules-colloids duality which yield extraordinary advantages in designing novel photocatalyst. Furthermore, introduction of inorganic ororganic functional groups enable these materials to act as metal dopant(s), ionic charge carriers or organo-crosslinker. As a result, structural properties and surface functionalities can be further tailored to attract desired molecules that involves in photocatalytic applications. In this review, we presented an integrated perspectives on specific 2D carbon family: graphene, graphitic carbon nitride and titanium carbide-MXenes that which were previously reviewed in isolation across separate review articles . Major discussions focus on the (i) processing technique for 2D material from pure solid form to colloidal suspension and (ii) criteria needs for facilitating charge transfer at 2D/2D interfaces. Overall, each of review section bridges the intrinsic properties of each class of 2D material and in the form 2D/2D hybrids together with their practical implementation in photocatalytic systems. We also addressed a critical research gap in understanding charge-carrier dynamics and offering some feasible strategies for photocatalytic material development tailored to environmental challenges.